Regulation of arterial pressure by the paraventricular nucleus in conscious rats: interactions among glutamate, GABA, and nitric oxide - Martins-Pinge, Marli C.; Mueller, Patrick J.; Foley, C M.; Heesch, Cheryl M.; Hasser, Eileen M. (Frontiers in Physiology, 2013)
The paraventricular nucleus (PVN) of the hypothalamus is an important site for autonomic and neuroendocrine regulation. Experiments in anesthetized animals and in vitro indicate an interaction among gamma-aminobutyric acid (GABA), nitric oxide (NO) and glutamate in the PVN. The cardiovascular role of the PVN and interactions of these neurotransmitters in conscious animals have not been evaluated fully. In chronically instrumented conscious rats, mean arterial pressure (MAP) and heart rate (HR) responses to microinjections (100 nl) in the region of the PVN were tested. Bilateral blockade of ionotropic excitatory amino acid (EAA) receptors (kynurenic acid, Kyn) in the PVN produced small but significant decreases in MAP and HR. GABAA receptor blockade (bicuculline, Bic), and inhibition of NO synthase (N-(G)-monomethyl-L-arginine, L-NMMA) each increased MAP and HR. The NO donor sodium nitroprusside (SNP) produced depressor responses that were attenuated by Bic. NO synthase inhibition potentiated both pressor responses to the selective EAA agonist, N-methyl-D-aspartic acid (NMDA), and depressor responses to Kyn. Increases in MAP and HR due to Bic were blunted by prior blockade of EAA receptors. Thus, pressor responses to GABA blockade require EAA receptors and GABA neurotransmission contributes to NO inhibition. Tonic excitatory effects of glutamate in the PVN are tonically attenuated by NO. These data demonstrate that, in the PVN of conscious rats, GABA, glutamate and NO interact in a complex fashion to regulate arterial pressure and heart rate under normal conditions.